The Use of E-CRM as a Means of Selling Groceries - Fatimah Syamsul; Nurwati; Wiwin Handoko (Jurnal Sistem Cerdas, 2024)
Customer Relationship Management (CRM) is a type of management regarding the management of a company with its customers to improve relationships with customers to maximize company growth. To implement Electronic-Customer Relationship Management (E-CRM), the role of information technology and human resources of the company is needed. E-CRM can make it easier for customers to get the necessary information from the company. Wholesale Berkat Doa is one of the basic food distributors that sells various kinds of basic necessities such as rice, oil and sugar which are the most demanded needs. To see these basic food products, customers must come directly to the store because there is no intermediary media to convey and provide product information to customers. The purpose of this research is to create an E-CRM system so that sales at Wholesale Blessing Doa can be done online. By implementing the E-CRM system, it can help Wholesir Berkat Doa to market and sell basic food products to customers. Customers know product information in detail and with CRM features namely members, discounts, promos, live chat, points, vouchers and reviews can maintain relationships with new and old customers which makes loyal customers to keep shopping at Wholesale Berkat Doa